Geostatistical analysis of Arabic coffee yield in two crop seasons - Luis C. C. Carvalho; Fabio M. da Silva; Gabriel A. e S. Ferraz; Juliana Stracieri; Patrícia F. P. Ferraz; Lucas Ambrosano (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT To make the coffee activity competitive, some farmers use precision coffee farming. Thus, it is possible to create thematic maps that guide management practices for regions where there are limitation for the plant development. The objective of this study was to identify the spatial dependence of coffee crop yield, in 2012 and 2013. The experimental area is located in a Haplustox in Três Pontas, Minas Gerais. One hundred sampling points were georeferenced for the collection of yield data through manual harvest. The difference of yield between crop seasons was also evaluated. Data were processed using geostatistical analysis. It was possible to identify and characterize the spatial dependence of all variables, as well as to create contour maps. There were differences between the 2012 and 2013 maps, due to the biennial coffee phenological cycle, which can be confirmed by the map of the difference between the crop seasons. It is recommended a crop management that considers the spatial variability of yield for greater economic return.